2008
DOI: 10.1002/jnr.21876
|View full text |Cite
|
Sign up to set email alerts
|

M4 muscarinic receptors are involved in modulation of neurotransmission at synapses of Schaffer collaterals on CA1 hippocampal neurons in rats

Abstract: All five subtypes of muscarinic acetylcholine receptors (mAChR; M(1)-M(5)) are expressed in the hippocampus, where they are involved both in cognitive functions and in synaptic plasticity, such as long-term potentiation (LTP). Muscarinic toxins (MTs) are small proteins from mamba snake venoms that display exquisite discrimination between mAChRs. MT1 acts as an agonist at M(1) and an antagonist at M(4) receptors, with similar affinities for both. MT3, the most selective antagonist available for M(4) receptors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 58 publications
(74 reference statements)
3
13
1
1
Order By: Relevance
“…Our results are consistent with data showing M4 receptors are present at high densities in stratum radiatum and that allosteric modulation of M4 receptors enhances carbachol-induced EPSP suppression (Shirey et al 2008). On the other hand, our data and those of Shirey et al (2008) contrast sharply with those of Sánchez et al (2009) who found pharmacological blockade of M4 receptors alone suppresses evoked Shaffer-collateral field potentials, suggesting that ambient endogenous ACh acting at M4 receptors potentiates glutamate release at this synapse. Discrepancies in results likely reflect critical differences in experimental setup, including the inclusion by Sánchez et al (2009) of the adenosine receptor agonist 2-chloroadenosine in the bath saline (which might occlude muscarinic suppression of EPSPs by activating presynaptic adenosine receptors; see Lupica et al 1992) and the use by Sánchez and colleagues of organotypic cultures rather than acute hippocampal slice preparations from more mature animals.…”
Section: Cholinergic Suppression Of Excitatory Synaptic Transmissioncontrasting
confidence: 56%
“…Our results are consistent with data showing M4 receptors are present at high densities in stratum radiatum and that allosteric modulation of M4 receptors enhances carbachol-induced EPSP suppression (Shirey et al 2008). On the other hand, our data and those of Shirey et al (2008) contrast sharply with those of Sánchez et al (2009) who found pharmacological blockade of M4 receptors alone suppresses evoked Shaffer-collateral field potentials, suggesting that ambient endogenous ACh acting at M4 receptors potentiates glutamate release at this synapse. Discrepancies in results likely reflect critical differences in experimental setup, including the inclusion by Sánchez et al (2009) of the adenosine receptor agonist 2-chloroadenosine in the bath saline (which might occlude muscarinic suppression of EPSPs by activating presynaptic adenosine receptors; see Lupica et al 1992) and the use by Sánchez and colleagues of organotypic cultures rather than acute hippocampal slice preparations from more mature animals.…”
Section: Cholinergic Suppression Of Excitatory Synaptic Transmissioncontrasting
confidence: 56%
“…In the striatum M 1 would amount about 57% and M 4 27%, and about 54 and 15%, respectively, in the amygdala [5]. There is a conspicuous expression of mAChR in both hippocampus and striatum, where many interneurons are cholinergic, compared to the amygdala.…”
Section: Introductionmentioning
confidence: 99%
“…Así mismo, recientemente se demostró el rol de m4 en la inhibición de la actividad de la adenilato ciclasa, así como en la modulación de la neurotransmisión de neuronas del hipocampo. Para tal fin se usó la propiedad antagonista de mt3 sobre los receptores mencionados [85,86].…”
Section: Toxinas De Venenos De Serpiente Como Herramientas En Investiunclassified